TRANSFORMASI STRATEGI SLA SEBAGAI UPAYA PENINGKATAN LAYANAN DAN KEPUASAN PELANGGAN PRODUK SURETY BOND DI PT ABC - Sovania, Erina; Oke Hasfiah; Jati Wahyono Agustinus (ITB AAS Indonesia Surakarta, 2025)
This study investigates the development of strategic alternatives to improve the Service Level Agreement (SLA) in marketing Suretybond products at PT ABC, the only state-owned guarantee company in Indonesia. The research was driven by the increasing market competition and operational inefficiencies observed in PT ABC’s Suretybond services, particularly regarding response time, service consistency, and customer satisfaction. Employing a qualitative-descriptive method, data were collected through literature review and in-depth interviews with key internal stakeholders. The SWOT analysis and Business Model Canvas were applied to identify internal and external strategic factors and to map the company's value creation process. The findings reveal key weaknesses in process integration, technological utilization, and service responsiveness, while opportunities lie in market expansion and digital innovation. A W-T (Weakness–Threat) strategy was selected to address operational inefficiencies and high market competition by enhancing SLA through improved document validation systems, technology-based services (e.g., Online Suretyship), and structured customer relationship management. The novelty of this research lies in integrating SWOT and Business Model Canvas to formulate a strategic model that is both practical and adaptive in increasing SLA performance and customer satisfaction. The results provide practical implications for guarantee service providers in improving service quality amid a dynamic business environment.